Immune-Active Microenvironment in Small Cell Carcinoma of the Ovary, Hypercalcemic Type: Rationale for Immune Checkpoint Blockade - Jelinic, Petar; Ricca, Jacob; Van Oudenhove, Elke; Olvera, Narciso; Merghoub, Taha; Levine, Douglas A; Zamarin, Dmitriy (JNCI : Journal of the National Cancer Institute, 2018)
Small cell carcinoma of the ovary, hypercalcemic type (SCCOHT), is a highly aggressive monogenic cancer driven by SMARCA4 mutations. Here, we report responses to anti-PD1 immunotherapy in four patients and characterize the immune landscape of SCCOHT tumors using quantitative immunofluorescence and gene expression profiling. Unexpectedly for a low mutation burden cancer, the majority of the tumors (eight of 11 cases) demonstrated PD-L1 expression with strong associated T-cell infiltration (R2 = 0.60-0.95). PD-L1 expression was detected in both tumor and stromal cells, with macrophages being the most abundant PD-L1-positive cells in some tumors (three of 11 cases). Transcriptional profiling revealed increased expression of genes related to Th1 and cytotoxic cell function in PD-L1-high tumors, suggesting that PD-L1 acts as a pathway of adaptive immune resistance in SCCOHT. These findings suggest that although SCCOHT are low-mutational burden tumors, their immunogenic microenvironment resembles the landscape of tumors that respond well to treatment with PD-1/PD-L1 blockade.